Essential differential diagnoses in the clinical evaluation of Acute Appendicitis (Research, Society and Development, 2024)
Introduction: Acute appendicitis (AA) occurs when there is an obstruction of the orifice of the vermiform appendix, resulting in progressive inflammation and distension that can compromise vascularization. Various mechanisms can result in acute abdominal pain or acute abdomen, requiring an understanding of the breadth of possible causes. Objective: To identify the main differential diagnoses that mimic the clinical presentation of AA and their possible patterns of differentiation. Materials and Methods: This is an integrative literature review. The PICO strategy was used to formulate the guiding question. Furthermore, the descriptors "Acute Appendicitis," "Differential Diagnosis," and "Clinical Presentation" were cross-referenced in the databases of the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar, and Virtual Health Library (BVS). Results and Discussion: It is essential that the clinical presentation of AA, as well as its laboratory and imaging findings, be well understood to identify possible variations that mimic the characteristic abdominal pain presentation, such as in cases of cecal and Meckel's diverticulitis, Crohn's disease, gynecological and obstetric conditions, mesenteric lymphadenitis, and renal colic. Conclusion: Detailed knowledge of differential diagnoses and the establishment of diagnostic hypotheses in appropriate cases is crucial for the proper clinical management of patients with acute abdominal pain, ensuring better outcomes and minimizing risks associated with erroneous diagnoses.